Non-intentional farm injury fatalities in NSW, Australia, 2001-2015 - Tony Lower; Margaret Rolfe; Noeline Monaghan (Sax Institute, 2017)
Background: Agriculture is one of the most hazardous industries in Australia. The Australian Centre for Agricultural Health and Safety is the only agency that records all non-intentional injury-related events (work and nonwork) on Australian farms. Materials and methods: Drawing on records from the National Coronial Information System, data for New South Wales (NSW), Australia, were analysed to assess cases in the 2001-2015 period. Each case was reviewed in accordance with the Farm Injury Optimal Dataset to ascertain gender, age, work relatedness and causal agents. The location of each incident was also mapped by Statistical Area Level 4. Denominator data on the number of agricultural establishments in each area and the number of workers involved in agriculture across all of NSW were sourced from the Australian Bureau of Statistics (ABS). Two-piece linear regressions using 2007 as the change point were completed to ascertain trends for the work-related cases and all deaths (work and nonwork). Differences in rates of all deaths by regions were assessed using Poisson regression models. Results: Results indicate no change in the rate of work-related deaths per 100 000 workers over the 15-year period (mean 17.3). Although there was a statistically significant reduction in all deaths (work and nonwork) per 10 000 farms through to 2007, the rate has remained stable since this time. There was no significant variation in the all-deaths rate (work and nonwork) between any of the geographic areas. Study limitations included estimations based on ABS data for the distribution of farms, the lack of data by statistical area on agricultural worker numbers and a case closure rate of 87%. Lessons learnt: There has been no improvement in work-related fatality rates in the sector in NSW for at least 15 years, and similarly no improvement in the all-injury fatality rate (work and nonwork) since 2007. Data in this study can be used to strengthen investment and revitalise the adoption of evidence based approaches that address relevant issues.